A multi-criteria approach to bid selection in public procurement - Plećić, Katarina; Žižović, Mališa; Marković, Marko; Đoković, Filip (Industrija, 2018)
Business forms such as the goods and services sales to state-owned enterprises, due to its secure billing, are extremely attractive for private businesses and as such are susceptible to possible misuse. When there is the possibility of corruption, regardless of whether it takes place, not only the protection of the procurers’ rights must be discussed, but also the protection of all parties involved in public procurement processes. The aim of this paper is to give a possible multi-criteria methodology for selecting the optimal of the submitted bids within the public procurement tender. According to the Public Procurement Law in Serbia, the procurement contracting authority is required to define the criteria for the winning tender with valued weights. The contribution of this paper lies within the new methodology which enables procurator to use transparent, unique and, by Public Procurement Law, correct way of choosing the best one from bids submitted within public procurement tender.
Keywords: Multi-criteria analysis; Public Procurement; Procurement